Dynamics Of Corporate Cash Holdings In Chinese Firms: An Empirical Investigation Of Asymmetric Adjustment Rate And Financial Constraints - Ajid , ur Rehman; Wang, Man; Kabiraj, Sajal (Asian Academy of Management (AAM), 2016)
Grounded in the notion of speed of adjustment this study investigates the adjustment rate of corporate cash holdings and financial constraints in Chinese firms. For this purpose data of 867 A-listed Chinese firms over a 14 years period (2001–2014) is analysed. The study applies Arellano and Bond (GMM2) and Blundell and Bond (GMM1) dynamic panel data model to investigate asymmetric speed of adjustment. We report considerable evidence about asymmetric adjustment of corporate cash holdings, i.e., downward adjustment rate is significantly higher than upward adjustment rate. This higher downward adjustment rate holds even after controlling for financial constraints. Moreover financial constraints also play an important role in dynamic cash adjustment. Financially unconstrained firms are found to adjust faster to their target cash holdings as compared to financially constrained firms. The high speed of adjustment for above target cash level firms holds even after controlling for financial constraints